Confucian freedom: assessing the debate - Carleo, Robert A. (Asian philosophy, 2021)
What place does freedom have in Confucianism? We find a wide spectrum of views on the matter: some deny that Confucians value or even conceive of freedom, while others celebrate uniquely exalted forms of Confucian freedom. This paper examines the range of proposals, finding consensus among these diverse views in that all identify distinctive Confucian emphases on (i) subjective affirmation of the good and (ii) the cultivation of desires and intentions to align with that good. The variation among views of Confucian freedom does not result from disparate interpretations of Confucian teachings. Rather, their divergence lies in affirming or denying that these core aspects of Confucian thought should be seen as ‘freedom.’ This reveals an undiscussed, fundamental question regarding Confucian freedom: Can and should we see the traditional Confucian moral ideal—that is, Confucian goodness and sagely virtue—as versions of freedom? What do we gain by doing so?